Optimizing School-Based Management to Improve Student Performance: a Review of the 2023 Curriculum - Wahyu Lestari; Febri Eka Mahendra; Norma Fitria; Zulkipli Jemain (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2024)
This study examines the optimization of school-based management (SBM) in improving student performance in the era of the 2023 curriculum. With the background of the importance of adapting to curriculum changes and the challenges faced in the education system, this research aims to identify effective SBM strategies and their impact on student performance. The methodology employed is qualitative research, utilizing data collection techniques such as interviews, questionnaires, observations, and document studies. The findings indicate that the implementation of SBM, which involves all stakeholders collaboratively, can significantly enhance student learning outcomes. Furthermore, this study provides recommendations for strengthening teacher training and increasing parental involvement in the educational process. The implications of this research emphasize the importance of sustaining SBM practices to create a responsive and adaptive learning environment and to achieve better educational goals in the future.